ABOUT THE UNIFORMITY AND THE STABILITY OF A VOLUME DISCHARGE IN HELIUM IN NEAR-ATMOSPHERIC PRESSURE - Vali Suliymanovich Kurbanismailov; Omar Alievich Omarov; Gadjimirza Balaglanovich Ragimkhanov; Abutrab Alexandrovich Aliverdiev (Acta Polytechnica, 2015)
We present experimental electric and time-spatial characteristics of a volume discharge and of the transition from a volume burning stage into a channel mode nearing atmospheric pressure. We show that the discharge uniformity rises with the increase of cathode spots density and gas pressure.